The Status of Himri Fish, Barbus luteus (Heckel) Population in the Al-Huwazah Marsh, South Iraq - Mohamed, Abdul-Razak M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
A total of 1647 specimens of himri Barbus luteus were used to describe the status of himri population in the Al-Huwazah marsh, south Iraq from October 2005 to December 2006. The relative abundance of B. luteus formed 29.4% of the total catch. The lengths of fish were ranged from 3.0cm to 35.0cm and the most dominant length groups observed were those of 11 to 21 cm. Total length-weight relationship was estimated as W = 0.0104 L3.084. The lengths of fish were 8.5, 15.5, 20.0, 24.0, 27.0, 29.0, 31.0, 32.5 and 33.5 cm at the end of 1-9 years respectively. Growth and mortality parameters estimated were: L∞= 37.0cm, K= 0.26, Z= 0.957, M= 0.336 and F= 0.621. Therefore, it may be claimed that the B. luteus in the Al-Huwazah marsh is being overfished, and a better management policy is necessary in this area.
Keywords: Himri barble Barbus luteus growth mortality marshes